Investigating Resulting Surface Topography and Residual Stresses in Bending DC01 Sheet Under Tension Friction Test - Krzysztof Szwajka; Tomasz Trzepieciński; Marek Szewczyk; Joanna Zielińska-Szwajka; Marek Barlak (Lubricants, 2025)
This article presents the results of experimental studies aimed at determining the values of residual stresses and coefficient of friction (CoF) in bending under tension friction test, which simulates friction conditions in sheet metal forming. The influence of surface modification of the countersample and CoFs between the countersample and DC01 steel sheet on the residual stress were analysed. This study also focused on the influence of surface modification of countersamples on the change of the main parameters of DC01 steel sheets. The hole-drilling method was used to determine residual stresses. Electron beam melting, lead-ion implantation and a combination of these two techniques were used to modify the surface layer of 145Cr6 steel countersamples. The maximum value of the CoF, about 0.31, was found for the electron beam melted countersample. As a result of the surface modification process, this countersample was characterised by the lowest value of average roughness, which directly influenced the increase in the real contact area. The occurrence of residual tensile stresses was observed near the surface layer of the sheet strip in contact with the countersample. With the increase of the considered depth of residual stress measurement, the residual tensile stresses were transformed into compressive residual stresses with a value between −75 and −50 MPa, depending on the type of friction pair. SEM analyses allowed us to identify two main friction mechanisms for all friction pairs: adhesion and abrasive wear.